Women work in folk crafts - Al Khalifa, Fadia Bint Abdullah; Al-Farih, Mona Ibrahim (Arab Journal for Sciences and Research Publishing, 2016)
The current study was conducted to document the wicker industry in Al-Ahsa governorate through: Recognition of the materials used in this industry, recognition of the wicker industry, recognition of the types of wicker industry products, and marketing of wicker products. Also the current study sought to discover the problems and obstacles that women face who are working in this industry, how do families accept women work in wicker industry, and how does working in such industry affects the social relationships between women and others. Furthermore determining the role of the government agencies and community institutions in supporting this industry and protecting it from disappearance. The study adopted a qualitative approach through the use of interview. The study found some results, the most important among them was that most of the women who are working in this industry were old ladies; therefore the wicker industry in Al-Ahsa is threatened with extinction. The ladies who are working in this industry face number of problems and obstacles that hinders their work, the most important was the absence of any official authority to be responsible of this industry, protecting it from extinction as it is a part of the Social authentic heritage of Saudi society.